2022
DOI: 10.1111/jmwh.13426
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Exposure to Chemicals in Household Products, Building Materials, Decoration, and Pesticides: Guidelines for Interventions During the Perinatal Period from the French National College of Midwives

Abstract: Introduction We are exposed to numerous pollutants inside our homes. The perinatal period represents a particular window of vulnerability during which these exposures can have negative health effects over a more or less long term. The objective of this article is to formulate guidelines for health care professionals and intended for parents to reduce exposure to chemical pollutants at home, based on the scientific literature and already existing guidelines. Methods We have followed the methodological procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…The CNGOF‐SFT guidelines issued in January 2020 also argued for a causal link between prenatal or postpartum exposure and SUID ( LE2 ) 39 . According to the 2016 national perinatal survey, 30% of the French women questioned reported having smoked just before their pregnancy and 16.5% were still smoking at least a cigarette a day in the third trimester 40 . Accordingly, action against this addiction should help to reduce the number of SUIDs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CNGOF‐SFT guidelines issued in January 2020 also argued for a causal link between prenatal or postpartum exposure and SUID ( LE2 ) 39 . According to the 2016 national perinatal survey, 30% of the French women questioned reported having smoked just before their pregnancy and 16.5% were still smoking at least a cigarette a day in the third trimester 40 . Accordingly, action against this addiction should help to reduce the number of SUIDs.…”
Section: Resultsmentioning
confidence: 99%
“…"Do not smoke in indoors at home and especially not in the bedroom" is a message that professionals must stress to parents. 40 Nonetheless, we do not consider that parental smoking status modifies the approach to counseling parents about sharing their room, since if the parents smoke, the infant has already acquired a considerable tobacco burden in utero, which continues with daily contact with parental clothing and exhaled breaths. These infants are therefore already at a higher risk of SUID.…”
Section: S88mentioning
confidence: 99%
“…Theme 3: Household Exposure to Substances Toxic for Pregnancy and Development ‐ Chapter n°4: Domestic Exposure to Chemicals: Household Products, Building Materials, Decoration, and Pesticides 25 ‐ Chapter n°5: Use of Cosmetic Products in Pregnant and Breastfeeding Women and Young Children 26 …”
Section: Methodsmentioning
confidence: 99%
“…Yet, PFAS is not the only chemical group of concern for human health. Humans are exposed to a plethora of chemical compounds on a regular basis, including industrial chemicals and chemicals found in building materials, household products, cosmetics and hygiene products, to name a few (Panico et al 2019;Rousseau et al 2022;Marroquin et al 2023). There consequently exists a need to understand, not only the potential effects of PFAS exposure on human health but also of possible combined effects that chemical mixtures may have on human health.…”
Section: General Conclusion and Future Perspectivesmentioning
confidence: 99%